Estrogen Acts Through Estrogen Receptor-β to Promote Mannan-Induced Psoriasis-Like Skin Inflammation - Wu, Huimei; Zeng, Longhui; Ou, Jiaxin; Wang, Tingting; Chen, Yong; Nandakumar, Kutty Selva (Frontiers in Immunology, 2022)
Sex-bias is more obvious in several autoimmune disorders, but not in psoriasis. However, estrogen levels fluctuate during puberty, menstrual cycle, pregnancy and menopause, which are related to variations in psoriasis symptoms observed in female patients. Estrogen has disease promoting or ameliorating functions based on the type of immune responses and tissues involved. To investigate the effects of estrogen on psoriasis, at first, we developed an innate immunity dependent mannan-induced psoriasis model, which showed a clear female preponderance in disease severity in several mouse strains. Next, we investigated the effects of endogenous and exogenous estrogen using ovariectomy and sham operated mice. 17-β-estradiol (E2) alone promoted the skin inflammation and it also significantly enhanced mannan induced skin inflammation. We also observed a prominent estrogen receptor-β (ER-β) expression in the skin samples, especially on keratinocytes. Subsequently, we confirmed the effects of E2 on psoriasis using ER-β antagonist (PHTPP) and agonist (DPN). In addition, estrogen was found to affect the expression of certain genes (vgll3 and cebpb), microRNAs (miR146a and miR21), immune cells (DCs and γδ T cells) as well as chemokines (CCL5 and CXCL10) and cytokines (TNF-α, IL-6, IL-22, IL-23 and IL-17 family), which promoted the skin inflammation. Thus, we demonstrate a pathogenic role for 17-β-estradiol in promoting skin inflammation, which should be considered while designing new treatment strategies for psoriasis patients.